Some issues in the study of pastoralists and the development of pastoralism - Helland, J. (International Livestock Centre for Africa, 1980)
General description of subsistence pastoral production systems w. ref. to livestock human ratio, population density, & animal population growth problems in east africa. Discussion of development planning for pastoral communities in relation to the role of social anthropology, citing examples from various areas spec. Turkana, Borana and Niger delta.